Antiplasmodial activity of aqueous extract of Berberis aristata roots against Plasmodium berghei-infected BALB/c mice. (2nd December 2015) - Chandel, Sanjeev; Bagai, Upma; Semwal, Ruchi Badoni; Semwal, Deepak Kumar
Abstract: Context : The rising problem of resistance to present antimalarial drugs stresses the need to look for newer antiplasmodial components with effective modes of action. The roots of Berberis aristata DC. (Berberidaceae) are used in the traditional medicine for malaria in various parts of India. Objective : The objective of this study was to evaluate antiplasmodial activity of B. aristata roots extract for the validation of its traditional medicinal use . Material and methods : Aqueous root extract of Berberis aristata (AREBA) was screened for its in vitro as well as in vivo antiplasmodial activity against lethal rodent malaria parasite Plasmodium berghei NK65. In vitro activity was evaluated against schizont maturation of P. berghei using various concentrations ranging from 1 to 100 µg/mL. For in vivo studies, AREBA at the doses of 150, 250, 350, and 650 mg/kg/d was administered to P. berghei infected BALB/c mice orally for 4 consecutive days (D0–D3). Results : AREBA showed in vitro antiplasmodial activity with an IC50 value of 40 µg/mL. In vivo studies demonstrated a variable dose-dependent chemosuppression with higher efficacy at lower doses. At a dose of 350 mg/kg/d, the suppressive and preventive activities were found to be 67.1% and 53.9%, respectively, followed by enhancing mean survival period up to 12.8 d for the curative assay versus 7.5 d for the untreated mice. Discussion and conclusion : These results provide relevant scientific evidences for the traditional medicinal use of this plant as malaria remedy and further advocates the isolation and characterization of active antiplasmodial principle from this plant.